Breastfeeding Behaviors and the Innate Immune System of Human Milk: Working Together to Protect Infants against Inflammation, HIV-1, and Other Infections - Henrick, Bethany M.; Yao, Xiao-Dan; Nasser, Laila; Roozrogousheh, Ava; Rosenthal, Kenneth L. (Frontiers in Immunology, 2017)
The majority of infants’ breastfeeding from their HIV-infected mothers do not acquire HIV-1 infection despite exposure to cell-free (CFV) and cell-associated virus (CAV) in HIV-infected breast milk. Paradoxically, exclusive breastfeeding (EBF) regardless of the HIV status of the mother has led to a significant decrease in mother-to-child transmission (MTCT) compared to non-exclusive breastfeeding (nEBF). Although it remains unclear how these HIV-exposed infants remain uninfected despite repeated and prolonged exposure to HIV-1, the low rate of transmission is suggestive of a multitude of protective, short-lived bioactive innate immune factors in breast milk. Indeed, recent studies of soluble factors in breast milk shed new light on mechanisms of neonatal HIV-1 protection. This review highlights the role and significance of innate immune factors in HIV-1 susceptibility and infection. Prevention of MTCT of HIV-1 is likely due to multiple factors, including innate immune factors such as lactoferrin and elafin among many others. In pursuing this field, our lab was the first to show that soluble TLR2 (sTLR2) directly inhibits HIV infection, integration and inflammation. More recently, we demonstrated that sTLR2 directly binds to selective HIV-1 proteins, including p17, gp41 and p24, leading to significantly reduced NFκB activation, IL-8 production, CCR5 expression and HIV-infection in a dose-dependent manner. Thus, a clearer understanding of soluble milk-derived innate factors with known anti-viral functions may provide new therapeutic insights to reduce vertical HIV-1 transmission, and will have important implications for protection against HIV-1 infection at other mucosal sites. Furthermore, innate bioactive factors identified in human milk may serve not only in protecting infants against infections and inflammation, but also the elderly; thus, opening the door for novel innate immune therapeutics to protect newborns, infants, adults and the elderly.